If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4y = 26 Solving 6x + -4y = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 6x + -4y + 4y = 26 + 4y Combine like terms: -4y + 4y = 0 6x + 0 = 26 + 4y 6x = 26 + 4y Divide each side by '6'. x = 4.333333333 + 0.6666666667y Simplifying x = 4.333333333 + 0.6666666667y
| 16x-13=2(3x-1) | | 5-6y+9y-15x+5x= | | (2x-9)2+(3x-14)2=(x-1)2 | | 11x-6-6x=14 | | -3.5-1.25x=-3.5 | | 11m+2-m+10= | | 5x-3x+2y+1= | | 3+(-7)=9(m+7) | | 2a-8=60 | | 4a+3b-2= | | -8(b+7)-5b= | | g(x)=.75x-5 | | 7/10+(-1/5)=x | | 8y(2x-3y)= | | 3n-5(5-7n)= | | 6(z-1)+7=2z+1 | | -4(y-9)(-y-1)=0 | | -5a(a+b)= | | 3(2x-7)=2(2x+1) | | (4+u)(4u+6)=0 | | (z+2)(z+9)=0 | | 7y+23=-3y | | (z+2)(z-9)=0 | | -4+4(3x-8)=6x-30 | | 14m-(2m+8)=0 | | -14z-4(2-5z)=-29 | | 4x+8y=180 | | -2(k+6)=-5 | | (2x-9)*2+(3x-14)*2=(x-1)*2 | | f(-2)=-8a+44-2b+4 | | -4(5x+7)= | | 164=8h+4h+50 |